Using Critical Thinking Technology in Teaching Idioms to University Students - Kalabaeva M. A (Researchparks Publishing, 2022)
This article deals with issues of teaching idioms applying critical thinking method as traditional method does not promote these skills. Critical thinking skills are of great importance as they are required to produce competent cadres for global market economy. Teachers should focus on students’ comprehending authentic speech and writing, additionally, think critically and analyze them.